Perbedaan perkembangan moral anak laki-laki dan anak perempuan pada usia Sekolah Dasar - Aswatun Hasanah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
The moral development of elementary school children is all the thoughts, feelings, and actions that exist in the period of school harmony or intellectual time by showing some traits such as honest, fair, respectful, helpful as a reference in acting. In the development of these children, the social world, namely the interaction between peers who can strengthen the understanding of moral principles such as reciprocal, cooperation, justice, and welfare. However it is slightly different when talking about moral developments in boys and moral developments in girls in elementary school age. The purpose of this research is to examine the moral development of boys and girls at elementary school age. The focus of the discussion on this study was the moral progression of elementary school age children, the moral development of boys and girls at elementary school age. The study used a qualitative approach with a literature study method. The results of the study expressed rejecting the moral development theory of Lawrance Kohlberg which says the moral reasoning of the boys is higher than the moral reasoning of the girls. There is a difference in the moral development of boys with girls as follows: 1) in acting boys lacking manners than girls. 2) The level of the male discipline is lower than the level of the daughter's discipline. 3) The boys pay less attention to the sound of conscience than girls 4) boys more often do a statement of regulations that apply than girls. 5) The level of honesty of lower boys is female Adri. 6.) Boys love to fight, have trouble, and engage in problems. 7) Girls prefer to invite to play with friends. 8) The little boy likes to help other people's work than girls who like to help other people's work.